Comparison of the psychometric properties of 3 pain scales used in the pediatric emergency department: Visual Analogue Scale, Faces Pain Scale-Revised, and Colour Analogue Scale. Issue 8 (August 2018) - Le May, Sylvie; Ballard, Ariane; Khadra, Christelle; Gouin, Serge; Plint, Amy C.; Villeneuve, Edith; Mâsse, Benoit; Tsze, Daniel S.; Neto, Gina; Drendel, Amy L.; Auclair, Marie-Christine; McGrath, Patrick J.; et al.
Abstract : Abstract: Appropriate pain measurement relies on the use of valid, reliable tools. The aim of this study was to determine and compare the psychometric properties of 3 self-reported pain scales commonly used in the pediatric emergency department (ED). The inclusion criteria were children aged 6 to 17 years presenting to the ED with a musculoskeletal injury and self-reported pain scores ≥30 mm on the mechanical Visual Analogue Scale (VAS). Self-reported pain intensity was assessed using the mechanical VAS, Faces Pain Scale-Revised (FPS-R), and Colour Analogue Scale (CAS). Convergent validity was assessed by Pearson correlations and the Bland–Altman method; responsiveness to change was assessed using paired sample t tests and standardized mean responses; and reliability was estimated using relative and absolute indices. A total of 456 participants were included, with a mean age of 11.9 years ± 2.7 and a majority were boys (252/456, 55.3%). Correlations between each pair of scales were 0.78 (VAS/FPS-R), 0.92 (VAS/CAS), and 0.79 (CAS/FPS-R). Limits of agreement (95% confidence interval) were −3.77 to 2.33 (VAS/FPS-R), −1.74 to 1.75 (VAS/CAS), and −2.21 to 3.62 (CAS/FPS-R). Responsiveness to change was demonstrated by significant differences in mean pain scores among the scales ( P < 0.0001). Intraclass correlation coefficient and coefficient of repeatability estimates suggested acceptable reliability for the 3 scales at, respectively, 0.79 and ±2.29 (VAS), 0.82 and ±2.07 (CAS), and 0.76 and ±2.82 (FPS-R). The scales demonstrated good psychometric properties for children with acute pain in the ED. The VAS and CAS showed a strong convergent validity, whereas FPS-R was not in agreement with the other scales. Abstract : Mechanical Visual Analogue Scale, Faces Pain Scale-Revised, and Colour Analogue Scale have strong responsiveness and reliability. A strong agreement was found between Visual Analogue Scale and Colour Analogue Scale.